Heavy Metals Bioaccumulation in Riparian Vegetation: A Multi-Species Biomonitoring Framework Using Total X-Ray Reflection Fluorescence Spectroscopy - Shakeel Ahmed Talpur; Simonetta Cristina Di Simone; Aziz Ahmed; Hafeez Ahmed Talpur; Muhammad Yousuf Jat Baloch; Francesco Stoppa; Luigi Menghini; Beatrice Maria Sole Giambastiani; Gianluigi Rosatelli (Environmental Processes, 2026)
Heavy metal contamination in Mediterranean riparian ecosystems presents serious risks to biodiversity and human health, requiring innovative biomonitoring methods for polluted watersheds. This study developed a comprehensive biomonitoring framework for an industrially impacted Mediterranean river basin, with approximately 100,000 tons of contaminated waste in landfills from decades of metallurgical processing. We investigated heavy metal bioaccumulation patterns in five taxonomically diverse native riparian species ( Equisetum arvense , Laurus nobilis , Rubus ulmifolius , Sambucus nigra , and Salix alba ) across contaminated and reference sites using Total Reflection X-ray Fluorescence (TXRF) spectroscopy. TXRF was validated against Inductively Coupled Plasma Atomic Optical Spectroscopy (ICP-AOS) using standard reference materials, demonstrating superior sensitivity for trace element detection in plant matrices. Heavy metal concentrations varied significantly among species and sites in riparian vegetation, with Fe (23.14 ± 5.21 mg/kg), Mn (2.74 ± 0.89 mg/kg), and Cr (3.33 ± 1.12 mg/kg) showing the highest accumulation. Laurus nobilis appeared as a multi-metal hyperaccumulator with the highest Pollution Load Index (PLI = 2.67) and exceptional accumulation of Cr (14.74 mg/kg) and Fe (63.64 mg/kg). Statistical analysis (Kruskal-Wallis test, p < 0.05) confirmed that Mn and Cr represented primary anthropogenic pollutants, with contaminated sites showing 2.20-fold and 1.92-fold increases, respectively. Principal Component Analysis revealed distinct co-accumulation networks, with Fe-Cr-Ni-Cu forming synchronized uptake mechanisms, while Mn operated independently. Biogeochemical ratio analyses (Fe/Zn, Cu/Mn) provided sensitive contamination indicators, detecting physiological stress beyond simple concentration measurements. Results support species-specific phytoremediation strategies aligned with UN Sustainable Development Goals, with Laurus suitable for multi-metal extraction and Equisetum for Mn-specific remediation, advancing sustainable environmental management in industrially impacted Mediterranean watersheds.

Cu-TiO2-Aluminosilicate Nanocomposite as Highly Efficient Photocatalyst for Sustainable Removal of Cefixime Antibiotic: Synthesis, Optimization, and Toxicity Evaluation - Muhammad Umar Farooq; Qurat-Ul-Ain; Muhammad Irfan Jalees; Mahnoor Abid; Mirza Nadeem Ahmad; Maira Kaleem; Asma Tufail Shah; Juan Joon Ching (Environmental Processes, 2024)

Drought Risk Analysis for Water Assessment at Gauged and Ungauged Sites in the Low Rainfall Regions of Pakistan - Hamd Ullah; Muhammad Akbar (Environmental Processes, 2021)

Exploring Water Consumption in Dhaka City Using Instrumental Variables Regression Approaches - Muhammad Shahadat Hossain Siddiquee; Raihan Ahamed (Environmental Processes, 2020)
This paper explores water consumption in Dhaka city for better understanding of its usage, and considers the implications of findings from distributive rationale. Using 459 household survey data collected by BRAC Institute of Governance and Development (BIGD), this study estimates income elasticities of water consumption after controlling the effects of other covariates including wealth-proxies, location, household size, water bill and spatial zones using the instrumental variable regression (IVREG) and instrumental variable quantile regression (IVQREG) approaches. The latter has an additive advantage over the former as the IVQREG provides a more accurate picture of the relationship of water consumption with the income throughout the entire water consumption distribution. Using the fixed pay variable as instrument, findings reveal the strong evidence that income is endogenous. The IVQREG results show that income elasticities are heterogeneous and vary significantly across the water quantiles, implying inequality in water consumption. It also provides strong systematic evidence as income elasticity of water consumption decreases with the increase in percentile. Significant spatial inequality in water consumption from IVREG approach disappears as we use IVQREG. This also strongly supports the systematic evidence obtained. Therefore, it is imperative to introduce different tariff structures among different water consumer groups for bringing equity in water consumption and revenue generation. However, Dhaka Water Supply & Sewerage Authority (DWASA) must ensure smart water meter before implementing such tariff structure as we face severe challenges while measuring residential water consumption.

Concomitant Treatment of Tannery and Paper Mill Effluents Using Extremely Metal-Tolerant Sulphate-Reducing Bacteria - Muhammad Muneeb; Muhammad Rashid; Arshad Javid; Syed Mohsin Bukhari; Waqas Ali; Ali Hasan; Muhammad Akmal; Ali Hussain (Environmental Processes, 2020)